Uniate Sacral Architecture in the Grand Duchy of Lithuania: A Synthesis of Confessional Architecture - Buržinskas Žygimantas (Sciendo, 2021)
The architectural legacy of the Unitarians in the former Grand Duchy of Lithuania has received little attention from researchers to this day. This article presents an architectural synthesis of the Uniate and Order of Basilians that reflected the old succession of Orthodox architectural heritage, but at the same time was increasingly influenced by the architectural traditions formed in Catholic churches. This article presents the tendencies of the development of Uniate architecture, paying attention to the brick and wooden sacral buildings belonging to the Uniate and Order of Basilians in the territory of the Grand Duchy of Lithuania. The early Uniate sacral examples reflected the still striking features of the synthesis, which were particularly marked in the formation of the Greek cross plan and apses in the different axes of the building. All this marked the architectural influences of Ukraine, Moldova and other areas of Central and South-Eastern Europe, which were also clearly visible in Orthodox architecture. Wooden Uniate architecture, as in the case of masonry buildings, had distinctly inherited features of Orthodox architecture, and in the late period, as early as the 18th century, there was a tendency to adopt the principles of Catholic church architecture, which resulted in complete convergence of most Uniate buildings with examples of Catholic church buildings. Vilnius Baroque School, formed in the late Baroque era, formed general tendencies in the construction of Uniate and Catholic sacral buildings, among which the clearer divisions of the larger structural and artistic principles are no longer noticeable in the second half of 18th century. The article also presents the image of baroque St. Nicholas Church, the only Uniate parish church in Vilnius city, which was lost after the reconstruction in the second half of the 19th century.